Lifeline as a narrative resource for socio-emotional formation in students of pedagogy (Praxis Educativa, 2019)
Results of experiences in the use of lifelines in higher education are presented. It is an autobiographical resource for the social construction of identity in initial teacher training. Likewise, it makes possible the reflection on the formative process in an intersubjective context. The methodology is qualitative, and experiences are analyzed on the elaboration and socialization of the lifeline. The participants were 60 students of Pedagogy in Special Education of the Catholic University of Temuco, Chile. The results show a narrative axis that articulates meanings and feelings during the elaboration process of lifeline. It is concluded that the lifeline is a resource for the recognition of oneself and others. This contributes to the development of reflective and socio-emotional skills. The collective dimension of the lifeline facilitates the emergence of empathy as a necessary competence for teacher training.
Keywords: teacher training; socio-emotional skills; lifeline; identity construction